Badges and Bongs: Police Officers’ Attitudes Toward Drugs - Cody Jorgensen (SAGE Open, 2018)
For unknown reasons, the research investigating police officers’ attitudes toward drug use is underdeveloped. One study, by Wilson, Cullen, Latessa, and Wills, has directly investigated police officers’ perceptions toward general vice crimes (including drug use) and perceived appropriate sanctions for committing these offenses. This article built upon that study. A survey measuring officers’ attitudes toward drugs was developed and used to gather data from a large metropolitan police department in the South. Responding officers displayed fairly serious and punitive attitudes toward drug offenses. In addition, they reported an interventionist attitude, believing that more can and should be done to control drug activity. Individual officer characteristics, such as education attainment and political ideology, were more strongly associated with drug attitudes than law enforcement indicators, such as rank and experience with the vice/narcotics unit.